Clima organizacional y satisfacción laboral de trabajadores civiles del ala aérea N°5 Loreto 2019 - Vasallo Ojea, Julio Daniel (2022)
The study problem was: Is there a relationship between the organizational climate and the satisfaction of the civil workers of the Air Wing N ° 5 Loreto 2019? The objective was to determine the relationship between the organizational climate and the satisfaction of civil workers of the Air Wing N ° 5 Loreto 2019.The study is quantitative with a correlational descriptive design, the population was 24 workers, the sample was 100% of the population. The technique was the survey and the instruments were two questionnaires, one on organizational work environment (Reliability 0.87% and Validity 0.84%) and the other on satisfaction (Reliability 0.89% and Validity 0.86%). The information processing was carried out using SPSS software version 24.0, the inferential test was Spearman's Rho Coefficient, with ? = 0.05. It was found in organizational climate that of 100.0% of the workers of the Air Wing No. 5 of Loreto, 62.5% stated that the organizational climate is medium, while 37.5% stated that it is unfavorable; 54.2% reported high job satisfaction in satisfaction, while 45.8% reported medium job satisfaction. When applying the Spearman Rho Coefficient, results were obtained that show a good significant statistical correlation between the organizational climate and job satisfaction Rho = 0.90 (p=0.001; valor < 0.05), which allows accepting the research hypothesis: There is a significant statistical relationship between the organizational climate and the work satisfaction of the civil workers of the Air Wing N ° 5 Loreto 2019.